Transcriptomic and Genetic Profiling of HIV-Associated Neurocognitive Disorders - Ojeda-Juárez, Daniel; Kaul, Marcus (Frontiers in Molecular Biosciences, 2021)
Early in the HIV pandemic, it became evident that people living with HIV (PLWH) develop a wide range of neurological and neurocognitive complications. Even after the introduction of combination antiretroviral therapy (cART), which dramatically improved survival of PLWH, the overall number of people living with some form of HIV-associated neurocognitive disorders (HAND) seemed to remain unchanged, although the incidence of dementia declined and questions about the incidence and diagnosis of the mildest form of HAND arose. To better understand this complex disease, several transcriptomic analyses have been conducted in autopsy samples, as well as in non-human primates and small animal rodent models. However, genetic studies in the HIV field have mostly focused on the genetic makeup of the immune system. Much less is known about the genetic underpinnings of HAND. Here, we provide a summary of reported transcriptomic and epigenetic changes in HAND, as well as some of the potential genetic underpinnings that have been linked to HAND, and discuss future directions with hurdles to overcome and angles that remain to be explored.